Activation of Cannabinoid Receptors Attenuates Endothelin-1–Induced Mitochondrial Dysfunction in Rat Ventricular Myocytes - Lu, Yan (J Cardiovasc Pharmacol, 2020)
Evidence suggests that the activation of the endocannabinoid system offers cardioprotection. Aberrant energy production by impaired mitochondria purportedly contributes to various aspects of cardiovascular disease. We investigated whether cannabinoid (CB) receptor activation would attenuate mitochondrial dysfunction induced by endothelin-1 (ET1). Acute exposure to ET1 (4 hours) in the presence of palmitate as primary energy substrate induced mitochondrial membrane depolarization and decreased mitochondrial bioenergetics and expression of genes related to fatty acid oxidation (ie, peroxisome proliferator–activated receptor-gamma coactivator-1α, a driver of mitochondrial biogenesis, and carnitine palmitoyltransferase-1β, facilitator of fatty acid uptake). A CB1/CB2 dual agonist with limited brain penetration, CB-13, corrected these parameters. AMP-activated protein kinase (AMPK), an important regulator of energy homeostasis, mediated the ability of CB-13 to rescue mitochondrial function. In fact, the ability of CB-13 to rescue fatty acid oxidation–related bioenergetics, as well as expression of proliferator-activated receptor-gamma coactivator-1α and carnitine palmitoyltransferase-1β, was abolished by pharmacological inhibition of AMPK using compound C and shRNA knockdown of AMPKα1/α2, respectively. Interventions that target CB/AMPK signaling might represent a novel therapeutic approach to address the multifactorial problem of cardiovascular disease.